2012
DOI: 10.1017/s1368980012001322
|View full text |Cite
|
Sign up to set email alerts
|

Improving children's dairy food and calcium intake: can intervention work? A systematic review of the literature

Abstract: Objective: Strategies are needed to address the shortfall in children's dairy food and Ca intakes. The present review identified interventions targeting an increase in children's dairy food or Ca intakes, and determined characteristics associated with successful intervention. Design: A systematic literature search identified fourteen intervention studies, published in English, between 1990 and 2010. Studies were evaluated for study population, setting and mode of delivery, dietary targets and outcome measures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 65 publications
3
55
5
Order By: Relevance
“…Behavior change strategies intended to improve dairy food and calcium intakes among early adolescent children were identified in a review of intervention studies. 17 These studies evaluated effectiveness of the strategies within an intervention, 17 however, motivation for engaging in the specific parenting practices was not explored. For example, nutritionists made milk available to Chilean children (8-10 years) through weekly home deliveries, provided instructions to parents about how children were to consume the milk, and encouraged parents to remove sugar-sweetened beverages from the home.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior change strategies intended to improve dairy food and calcium intakes among early adolescent children were identified in a review of intervention studies. 17 These studies evaluated effectiveness of the strategies within an intervention, 17 however, motivation for engaging in the specific parenting practices was not explored. For example, nutritionists made milk available to Chilean children (8-10 years) through weekly home deliveries, provided instructions to parents about how children were to consume the milk, and encouraged parents to remove sugar-sweetened beverages from the home.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing intake of dairy products will help improve intakes of a range of important nutrients, particularly calcium and magnesium that were especially lacking compared to recommended intakes in our subject group. A recent review identified taste exposure and prompting practice as important strategies utilised in effective interventions to increase calcium or dairy intake, along with concentrated delivery across a variety of settings [58]. …”
Section: Discussionmentioning
confidence: 99%
“…This review is limited to studies targeting adolescents aged 12 to 18 years, as this is a crucial period of growth, and a period of dietary self-efficacy development. This analysis will complement the systematic review of dietary interventions to increase dairy consumption among children (aged up to 12 years), by Hendrie et al 2 Results of this review will facilitate the development of interventions that target adolescents, with the goals of combating insufficient dairy intake.…”
mentioning
confidence: 92%